2009
DOI: 10.1161/circulationaha.109.876706
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Infusion of Streptokinase for the Treatment of Left-Sided Prosthetic Valve Thrombosis

Abstract: Background— No large prospective studies have evaluated the efficacy of fibrinolytic therapy for left-sided prosthetic valve thrombosis, yet it remains the first line of treatment in developing countries. Methods and Results— We performed a randomized controlled trial comparing an accelerated infusion with the conventional infusion of streptokinase in 120 patients with a first episode of left-sided prosthetic val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 24 publications
3
55
2
Order By: Relevance
“…In general, TT for the treatment of PVT in nonpregnant patients is successful in ≈85% of patients. [36][37][38][39][40][41][42][43] On the other hand, our protocol demonstrated a complete success rate among all pregnant patients with PVT. This could be explained by the fresh and rapid development of clot in this specific patient population compared with nonpregnant patients with gradually developed and organized thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…In general, TT for the treatment of PVT in nonpregnant patients is successful in ≈85% of patients. [36][37][38][39][40][41][42][43] On the other hand, our protocol demonstrated a complete success rate among all pregnant patients with PVT. This could be explained by the fresh and rapid development of clot in this specific patient population compared with nonpregnant patients with gradually developed and organized thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe MR who develop an EF ≤60% or LVESD ≥40 have already developed LV systolic dysfunction. [112][113][114][115] One study has suggested that for LV function and size to return to normal after mitral valve repair, the left ventricular ejection fraction (LVEF) should be >64% and LVESD <37 mm. 112 Thus, when longitudinal follow-up demonstrates a progressive decrease of EF toward 60% or a progressive increase in LVESD approaching 40 mm, it is reasonable to consider intervention.…”
Section: Iia Bmentioning
confidence: 99%
“…Despite that accelerated protocols are attractive because they might achieve more rapid lysis of the thrombus, they increase the risk of serious bleeding and embolic events. 29 Keeping with this, recent data proposed that low dose of rt-PA (25 mg) and slow infusion (6 hours) resulted in mortality benefit derived from the lower rates of bleeding and systemic thromboembolism. 30 Serial TTE during the infusion allows the reassessment of thrombus resolution.…”
Section: Thrombolysis In Left-sided Opvtmentioning
confidence: 99%